Folic acid in the prophylactic medicine - Polka, O.O.; Omelchenko, E.M.; Kachko, H.O.; Pedan, L.R. (Environment & Health, 2017)
Purpose: evaluation folic acid fortification of flour as a method of mass prophylaxis of congenital pathology. Materials and methods: analytic, bibliographic. Results. There is evidence of a reduced risk of congenital neural tube defects in children born to women who took 800 micrograms of folic acid in the preconception period. To the development of the insufficiency of this vitamin can result in a low content of food, a dysbacteriosis of various etiologies (for example, prolonged intake of sulfonamides) and a disturbance in the metabolism of folic acid, which changes during carrier С677Т and А1298С polymorphisms of the gene of methylenetetrahydrofolatereductase (MTHR). The frequency of MTHFR with reduced activity in Ukraine is quite high. At the population level, this leads to inefficiency of its use and toxicity, as the accumulation of folate metabolites leads to the development of dyspeptic phenomena, allergic reactions and vitamin deficiency B12. Consequently, its use for prophylactic purposes requires an individual approach to each patient, especially when considering the possible carriage of allelic variants of the MTHFR gene. Their prevalence in the territory of Ukraine and clinical significance for today remains insufficiently investigated. Conclusion. We consider it advisable to conduct large-scale research in Ukraine on the content of folate in the diet, digestibility and content in blood plasma in different age groups. Received results will be an evidence base for decision about fortification.